Composite anion adsorbent as well as preparation method and application thereof
By preparing composite anion adsorbents, using multivalent metal ions of different compound valences for hydrolysis and treatment, the problems of low selectivity for vanadium resource recovery and low process efficiency in the prior art are solved, and efficient and stable vanadium resource adsorption and recovery effect are achieved.
Patent Information
- Application Number
- CN202411964777.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
In the prior art, when recovering vanadium resources from vanadium-containing wastewater, stone coal vanadium extraction leaching solution and sodium chromate leaching solution, there are problems such as low selectivity, long process flow, low production efficiency and the generation of hazardous solid waste.
A composite anion adsorbent is used, which mixes and hydrolyzes the metal ion solution containing polyvalent metal ions of different compound valences with alkali liquid to form a hydrated oxide precursor with a large specific surface area and a high adsorption active site. After aging and activation treatment, an adsorbent with high selectivity and high adsorption capacity is obtained.
This adsorbent can maintain high stability under different pH conditions and has a high selective adsorption effect. It is suitable for the adsorption and recovery of vanadium resources in vanadium-containing wastewater, stone coal vanadium extraction leaching solution and sodium chromate leaching solution under various conditions. It has a simple process and low cost.
Smart Images

Figure CN119771340A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical metallurgy, and specifically relates to a composite anion adsorbent and a preparation method and application thereof. Background Art
[0002] Vanadium is an important strategic resource, widely used in the fields of steel, cutting-edge defense technology, chemical industry, and light textile industry. Vanadium resources mainly exist in minerals such as vanadium-titanium magnetite, vanadium-uranium ore, vanadium-lead ore, and stone coal vanadium ore. With the continuous expansion of the application fields and market demand of vanadium and its compounds, vanadium resources are decreasing day by day, and the vanadium industry is developing rapidly. The amount and types of vanadium-containing wastewater generated are also increasing. For example: due to the low vanadium content of stone coal vanadium ore, the vanadium concentration in its leachate is also low, and enrichment and recovery methods are usually required to extract vanadium resources. Chromite is often accompanied by vanadium components. During the calcium-free roasting and leaching process, vanadium will enter the sodium chromate leaching solution. As an impurity, it will affect the properties of the chromium salt product, so it often needs to be purified. In summary, it can be seen that it is of great significance to recover vanadium resources from vanadium-containing wastewater, stone coal vanadium extraction leaching solution, and sodium chromate leaching solution.
[0003] At present, the main method for recovering vanadium resources from vanadium-containing wastewater, stone coal vanadium leaching solution and sodium chromate leaching solution is chemical precipitation. Chemical precipitation methods generally include the following three methods: the first method is to add a reducing agent to reduce pentavalent vanadium to low-valent vanadium for precipitation, and then oxidize and leach the low-valent vanadium; the second method is to add excess calcium oxide to generate calcium vanadate precipitation, and then carbonate and leach the calcium vanadate precipitation; the third method is to add an adsorbent for selective recovery of vanadium resources.
[0004] Although the above chemical precipitation method can achieve a good effect of recovering vanadium resources, there are some problems: first, the reduction precipitation method is not suitable for precipitating low-valent vanadium from high-concentration sodium chromate leachate; second, although the method of adding excess calcium oxide to precipitate calcium vanadate is effective, the amount of calcium oxide added is often more than 10 times the theoretical amount, and it is only applicable to strong alkaline solutions. In addition, both of the above two chemical precipitation methods also have problems such as long process flow and low production efficiency, and both have no ion selectivity. This is because vanadium ions and chromium ions co-exist in vanadium-containing wastewater and sodium chromate leachate, resulting in the co-precipitation of vanadium and chromium during the treatment process, thereby producing a large amount of V 5+ / Cr 6+ Hazardous solid waste.
[0005] The adsorption method is currently the most studied. For example, Chinese patents CN111455163A and CN101760651A both use alkaline anion exchange resins to adsorb and recover vanadium when treating acid leaching solution for extracting vanadium from stone coal. Chinese patent CN102337411A also discloses a method for recovering vanadium and chromium from high-chromium and low-vanadium vanadium precipitation wastewater, which specifically uses weakly alkaline or strongly alkaline ion exchange resins to adsorb vanadium and chromium in the wastewater. However, the existing resins for recovering vanadium by adsorption have poor selectivity.
[0006] In order to further improve the adsorption selectivity of vanadium ions, Chinese patent CN116715270A discloses a method for removing impurity ions in sodium dichromate mother liquor by using hydrated chromium oxide, specifically using hydrated chromium oxide to absorb and recover vanadium resources in sodium dichromate crystallization mother liquor; Chinese patent CN113198414A also discloses a hydrated chromium oxide adsorbent, which uses hydrated chromium oxide to adsorb vanadium in sodium chromate leachate. Although hydrated chromium oxide has good adsorption selectivity, it is synthesized by using pure substances, resulting in high production costs.
[0007] Based on this, in this field, there is an urgent need to solve how to prepare adsorbent materials with both high adsorption selectivity and high adsorption capacity at low cost to solve the above problems. Summary of the invention
[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a composite anion adsorbent and a preparation method and application thereof. The preparation method of the composite anion adsorbent provided by the present invention is simple and low-cost, and the overall process is clean and pollution-free. At the same time, the obtained composite anion adsorbent has high selectivity and high adsorption capacity, so the preparation method provided by the present invention has broad application prospects.
[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a method for preparing a composite anion adsorbent, the method comprising the following steps:
[0011] S1. A metal ion solution containing a first polyvalent metal ion and a second polyvalent metal ion is mixed and hydrolyzed with an alkali solution to obtain a precursor, wherein the valence of the first polyvalent metal ion is different from the valence of the second polyvalent metal ion;
[0012] S2. The precursor and the original solution to be adsorbed are mixed, and the composite anion adsorbent is obtained after aging and activation treatment in sequence.
[0013] The present invention utilizes a mixed solution of multivalent metal ions with different valences to prepare a composite anion adsorbent. First, a metal ion solution containing a first multivalent metal ion and a second multivalent metal ion is rapidly hydrolyzed to obtain a hydrated oxide precursor with a large specific surface area and a high adsorption active site. Secondly, the hydrated oxide precursor and the original solution to be adsorbed are mixed and aged to greatly improve the stability and adaptability of the adsorbent. Finally, the adsorption sites of the aged adsorbent are activated to obtain a composite anion adsorbent with high adsorption selectivity, high adsorption capacity and low cost.
[0014] In addition, the composite anion adsorbent prepared by the present invention can be applied to the adsorption and recovery of vanadium resources in vanadium-containing wastewater, stone coal vanadium extraction leaching solution and sodium chromate leaching solution under various conditions (pH value is in the range of 2-12), and the adsorbent can not only maintain high stability under different pH conditions, but also has a highly selective adsorption effect.
[0015] Preferably, in step S1, the first multivalent metal ions include trivalent metal ions.
[0016] Preferably, the trivalent metal ion includes any one of chromium ion, iron ion or aluminum ion, or a combination of at least two of them. Typical but non-limiting examples of the combination include: a combination of chromium ion and aluminum ion, a combination of iron ion and aluminum ion, a combination of chromium ion and iron ion, and a combination of chromium ion, iron ion and aluminum ion, etc.
[0017] Preferably, the concentration of trivalent metal ions in the metal ion solution is 0.01mol / L-1.5mol / L, for example, it can be 0.01mol / L, 0.02mol / L, 0.05mol / L, 0.08mol / L, 0.1mol / L, 0.2mol / L, 0.5mol / L, 0.8mol / L, 1.0mol / L, 1.1mol / L, 1.2mol / L, 1.3mol / L, 1.4mol / L, 1.5mol / L, etc.
[0018] Preferably, the second multivalent metal ions include divalent metal ions.
[0019] Preferably, the divalent metal ions include magnesium ions and / or calcium ions.
[0020] Preferably, the molar ratio of the second polyvalent metal ion to the first polyvalent metal ion is (0.01-1):1, preferably (0.05-0.3):1, for example, 0.01:1, 0.02:1, 0.05:1, 0.08:1, 0.1:1, 0.12:1, 0.15:1, 0.18:1, 0.2:1, 0.22:1, 0.25:1, 0.28:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, etc. The present invention controls the molar ratio of the second polyvalent metal ion to the first polyvalent metal ion so that the lattice integrity of the hydrated oxide of the first polyvalent metal ion is suppressed during the hydrolysis process, and finally a non-crystalline hydrated oxide can be generated. If the molar ratio of the second polyvalent metal ion to the first polyvalent metal ion is low, the effect of inhibiting the lattice integrity of the hydrated oxide of the first polyvalent metal ion during the hydrolysis process will be reduced, and a small amount of crystalline hydrated oxide will be produced, thereby affecting the adsorption effect; if the molar ratio of the second polyvalent metal ion to the first polyvalent metal ion is high, the proportion of water and oxide generated by the first polyvalent metal ion during the hydrolysis process will be low, thereby affecting the adsorption effect.
[0021] Preferably, the concentration of the alkali solution in step S1 is 1mol / L-20mol / L, preferably 5mol / L-15mol / L, for example, it can be 1mol / L, 2mol / L, 4mol / L, 5mol / L, 6mol / L, 8mol / L, 10mol / L, 11mol / L, 13mol / L, 15mol / L, 18mol / L, 20mol / L, etc.
[0022] Preferably, the mixed hydrolysis method in step S1 includes adding a metal ion solution containing the first polyvalent metal ion and the second polyvalent metal ion to an alkaline solution, or adding the alkaline solution to a metal ion solution containing the first polyvalent metal ion and the second polyvalent metal ion, or adding the metal ion solution containing the first polyvalent metal ion and the second polyvalent metal ion and the alkaline solution in parallel, preferably adding the metal ion solution containing the first polyvalent metal ion and the second polyvalent metal ion to the alkaline solution.
[0023] Preferably, the time for the mixed hydrolysis in step S1 is 0.1h-2h, preferably 0.2h-1h, for example, it can be 0.1h, 0.2h, 0.5h, 0.8h, 1h, 1.2h, 1.5h, 1.8h, 2h, etc.
[0024] Preferably, the temperature of the mixed hydrolysis in step S1 is 25°C-95°C, preferably 50°C-80°C, for example, it can be 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, etc.
[0025] Preferably, the pH value of the mixed hydrolysis in step S1 is 5-14, for example, it can be 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, etc.
[0026] Preferably, solid-liquid separation is performed immediately after the mixed hydrolysis in step S1 is completed.
[0027] As a preferred technical solution of the present invention, on the one hand, by further regulating the addition method of the metal ion solution containing the first multivalent metal ion and the second multivalent metal ion into the alkaline solution, the multivalent metal ions with different valences can undergo a rapid hydrolysis reaction, thereby generating a disordered, small and non-crystalline hydrated oxide precursor, and the above-mentioned hydrated oxide precursor has a large specific surface area and more active and selective adsorption sites; on the other hand, the present invention further regulates the hydrolysis temperature and pH value, which can further accelerate the hydrolysis reaction rate. Since crystalline hydrates can be generated under the conditions of the preferred hydrolysis temperature and pH value, but the multivalent metal ions with different valences have different radii, the low-valent metal ions replace the high-valent metal ions during hydrolysis, resulting in the deterioration of the integrity of the high-valent metal ion hydrated oxide lattice, thereby continuously generating non-crystalline hydrates.
[0028] It can be seen that the preparation method provided by the present invention can achieve a rapid hydrolysis reaction and avoid the formation of crystalline hydrated oxides under the synergistic effect of many factors such as the preferred molar ratio of multivalent metal ions with different valences, hydrolysis temperature, pH value, mixing time, and immediate solid-liquid separation after the mixed hydrolysis.
[0029] Preferably, the raw solution to be adsorbed in step S2 includes any one of vanadium-containing wastewater, stone coal vanadium extraction leaching solution or sodium chromate leaching solution.
[0030] Preferably, the pH value of the raw solution to be adsorbed in step S2 is 2-12, for example, it can be 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0031] Preferably, the aging temperature in step S2 is 25°C-95°C, preferably 50°C-80°C, for example, it can be 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, etc.
[0032] Preferably, the aging time in step S2 is 1 h-10 h, for example, it can be 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, etc.
[0033] Preferably, after the aging in step S2 is completed, a washing treatment is performed to remove the residual raw solution to be adsorbed.
[0034] In the present invention, the small-particle, non-crystalline and large-specific-surface-area hydrated oxide precursor generated after the hydrolysis reaction has a large number of hydroxyl active adsorption sites. When aged in the stock solution to be adsorbed, the hydroxyl in the hydrated oxide precursor preferentially undergoes coordination exchange with the vanadate anion, and under the combined effect of the composition, pH value and aging temperature of the preferred stock solution to be adsorbed, the adaptability of the hydrated oxide precursor to other components, pH value and temperature in the stock solution to be adsorbed is further improved, thereby enhancing the stability of the hydrated oxide precursor in the stock solution to be adsorbed.
[0035] Preferably, the activation reagent in step S2 comprises alkaline solution.
[0036] Preferably, the mass concentration of the alkali solution used for the activation in step S2 is 2%-10%, for example, it can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc.
[0037] Preferably, the activation temperature in step S2 is 25°C-95°C, preferably 25°C-50°C, for example, it can be 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, etc.
[0038] Preferably, the activation time in step S2 is 1 h-10 h, for example, it can be 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, etc.
[0039] Preferably, after the activation in step S2 is completed, washing treatment is performed to remove residual alkali solution.
[0040] In the present invention, the hydroxyl groups in the hydrated oxide precursor will undergo coordination exchange with the vanadate anions in the original solution to be adsorbed during the aging process, and then an alkali solution will be used to exchange with the coordinated vanadate anions during the desorption process of the activation treatment, thereby obtaining a composite anion adsorbent having a large number of highly active hydroxyl adsorption sites, high selectivity and high stability.
[0041] In the present invention, the washing liquid in the overall preparation process is recycled into the system after water treatment, and the water in the aging process is recycled into the adsorption stock liquid system.
[0042] In the present invention, the alkali solution is sodium hydroxide solution, and other types such as sodium carbonate, ammonia water, etc. are also applicable.
[0043] As a preferred technical solution of the present invention, the method comprises the following steps:
[0044] S1. A metal ion solution containing trivalent metal ions and divalent metal ions is added to an alkali solution with a concentration of 5mol / L-15mol / L for mixed hydrolysis, wherein the concentration of the trivalent metal ions is 0.01mol / L-1.5mol / L, the molar ratio of the divalent metal ions to the trivalent metal ions is (0.05-0.3): 1, the mixed hydrolysis time is 0.2h-1h, the mixed hydrolysis temperature is 50°C-80°C, the mixed hydrolysis pH is 5-14, and the mixed hydrolysis is immediately separated into solid and liquid to obtain a precursor;
[0045] S2. Add the precursor to the original solution to be adsorbed, the pH value of the original solution to be adsorbed is 2-12, and age it at 50℃-80℃ for 1h-10h, wash it after aging, and then add alkaline solution with a mass concentration of 2%-10%, activate it at 25℃-50℃ for 1h-10h, wash it after activation to obtain the composite anion adsorbent.
[0046] Preferably, the composite anion adsorbent selectively adsorbs at least one of vanadate, silicate, phosphate or arsenate.
[0047] In a second aspect, the present invention provides a composite anion adsorbent, wherein the composite anion adsorbent is prepared by the method for preparing a composite anion adsorbent according to the first aspect.
[0048] Preferably, the particle size of the composite anion adsorbent is 1 nm-5 nm, for example, 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, etc.
[0049] Preferably, the specific surface area of the composite anion adsorbent is 380 m 2 / g-473m 2 / g, for example, 380m 2 / g, 390m 2 / g, 400m 2 / g, 410m 2 / g, 420m 2 / g, 430m 2 / g, 440m 2 / g, 450m 2 / g, 460m 2 / g, 470m 2 / g, 473m 2 / g, etc.
[0050] In a third aspect, the present invention provides an application of the composite anion adsorbent according to the first aspect, wherein the composite anion adsorbent is used to adsorb and recover vanadium from any one of vanadium-containing wastewater, stone coal vanadium extraction leaching solution or sodium chromate leaching solution.
[0051] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0052] Compared with the prior art, the present invention provides a method for preparing a composite anion adsorbent, and has the following beneficial effects:
[0053] (1) First, the present invention utilizes a mixed solution of multivalent metal ions with different valences for rapid hydrolysis to prepare a hydrated oxide precursor having small particle size, non-crystalline and large specific surface area; secondly, the stability and adaptability of the hydrated oxide precursor are further improved through aging treatment; in addition, the aged hydrated oxide precursor is subjected to activation treatment to finally obtain a composite anion adsorbent having high adsorption capacity, high adsorption selectivity and high stability.
[0054] (2) The composite anion adsorbent prepared by the present invention can be applied to the adsorption and recovery of vanadium resources in vanadium-containing wastewater, stone coal vanadium extraction leaching solution and sodium chromate leaching solution under various conditions (pH value is in the range of 2-12), and the adsorbent can not only maintain high stability under different pH conditions, but also has a highly selective adsorption effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 This is a process flow chart of the method for preparing a composite anion adsorbent provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0056] The technical solution of the present invention is further described below by combining the accompanying drawings and specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0057] Example 1
[0058] This embodiment provides a composite anion adsorbent and a preparation method thereof, such as Figure 1 As shown, the preparation method comprises the following steps:
[0059] S1. A metal ion solution containing trivalent chromium ions, iron ions, divalent calcium ions and magnesium ions is added to a sodium hydroxide solution with a concentration of 5 mol / L for mixed hydrolysis, wherein the concentration of the trivalent metal ions is 0.5 mol / L, the molar ratio of the divalent metal ions to the trivalent metal ions is 0.1:1, the mixed hydrolysis time is 0.4 h, the mixed hydrolysis temperature is 50 ° C, the mixed hydrolysis pH is 11, and the mixed hydrolysis is immediately separated from the solid and liquid and washed to obtain a precursor;
[0060] S2. The precursor was added to a sodium chromate leachate with a pH value of 10 and aged at 80°C for 2 hours. After the aging, the residual sodium chromate leachate was washed with water, and then a sodium hydroxide solution with a mass concentration of 3% was added and activated at 40°C for 2 hours. After the activation, the residual sodium hydroxide solution was washed with water to obtain a particle size of 1.5 nm and a specific surface area of 435 m 2 / g of the composite anion adsorbent.
[0061] Example 2
[0062] This embodiment provides a composite anion adsorbent and a preparation method thereof, the preparation method comprising the following steps:
[0063] S1. A metal ion solution containing trivalent chromium ions, iron ions and aluminum ions and divalent calcium ions and magnesium ions is added to a sodium hydroxide solution with a concentration of 3 mol / L for mixed hydrolysis, wherein the concentration of the trivalent metal ions is 0.1 mol / L, the molar ratio of the divalent metal ions to the trivalent metal ions is 0.01:1, the mixed hydrolysis time is 0.6 h, the mixed hydrolysis temperature is 95 ° C, the mixed hydrolysis pH is 5, and the mixed hydrolysis is immediately separated from the solid and liquid and washed to obtain a precursor;
[0064] S2. The precursor was added to vanadium-containing wastewater with a pH value of 9 and aged at 60°C for 5 hours. After the aging, the residual vanadium-containing wastewater was washed with water, and then a sodium hydroxide solution with a mass concentration of 10% was added and activated at 30°C for 3 hours. After the activation, the residual sodium hydroxide solution was washed with water to obtain a particle size of 2nm and a specific surface area of 410m 2 / g of the composite anion adsorbent.
[0065] Example 3
[0066] This embodiment provides a composite anion adsorbent and a preparation method thereof, the preparation method comprising the following steps:
[0067] S1. A sodium hydroxide solution having a concentration of 1 mol / L is added to a metal ion solution containing trivalent chromium ions, aluminum ions and divalent calcium ions for mixed hydrolysis, wherein the concentration of the trivalent metal ions is 0.01 mol / L, the molar ratio of the divalent metal ions to the trivalent metal ions is 0.3:1, the mixed hydrolysis time is 1 h, the mixed hydrolysis temperature is 70 ° C, the mixed hydrolysis pH is 12, and the mixed hydrolysis is immediately followed by solid-liquid separation and washing to obtain a precursor;
[0068] S2. The precursor was added to the stone coal vanadium extraction leaching solution with a pH value of 2, and aged at 25°C for 10 hours. After the aging, the residual stone coal vanadium extraction leaching solution was washed with water, and then a sodium hydroxide solution with a mass concentration of 2% was added, and activated at 50°C for 1 hour. After the activation, the residual sodium hydroxide solution was washed with water to obtain a particle size of 4nm and a specific surface area of 383m 2 / g of the composite anion adsorbent.
[0069] Example 4
[0070] This embodiment provides a composite anion adsorbent and a preparation method thereof, the preparation method comprising the following steps:
[0071] S1. A metal ion solution containing trivalent chromium ions and divalent calcium ions is added to a sodium hydroxide solution having a concentration of 20 mol / L for mixed hydrolysis, wherein the concentration of the trivalent metal ions is 1 mol / L, the molar ratio of the divalent metal ions to the trivalent metal ions is 0.5:1, the mixed hydrolysis time is 0.1 h, the mixed hydrolysis temperature is 80 ° C, the mixed hydrolysis pH is 9, and the mixed hydrolysis is immediately followed by solid-liquid separation and washing to obtain a precursor;
[0072] S2. The precursor was added to a sodium chromate leachate with a pH value of 12 and aged at 60°C for 1 hour. After the aging, the residual sodium chromate leachate was washed with water, and then a sodium hydroxide solution with a mass concentration of 5% was added and activated at 25°C for 8 hours. After the activation, the residual sodium hydroxide solution was washed with water to obtain a particle size of 3.2 nm and a specific surface area of 391 m 2 / g of the composite anion adsorbent.
[0073] Example 5
[0074] This embodiment provides a composite anion adsorbent and a preparation method thereof, the preparation method comprising the following steps:
[0075] S1. A metal ion solution containing trivalent iron ions and divalent calcium ions and magnesium ions is added to a sodium hydroxide solution with a concentration of 10 mol / L for mixed hydrolysis, wherein the concentration of the trivalent metal ions is 0.2 mol / L, the molar ratio of the divalent metal ions to the trivalent metal ions is 0.05:1, the mixed hydrolysis time is 2 h, the mixed hydrolysis temperature is 25 ° C, the mixed hydrolysis pH is 8, and the mixed hydrolysis is immediately followed by solid-liquid separation and washing to obtain a precursor;
[0076] S2. The precursor was added to a sodium chromate leachate with a pH value of 8, and aged at 75°C for 3 hours. After the aging, the residual sodium chromate leachate was washed with water, and then a sodium hydroxide solution with a mass concentration of 6% was added, and activated at 95°C for 4 hours. After the activation, the residual sodium hydroxide solution was washed with water to obtain a particle size of 4.7nm and a specific surface area of 473m 2 / g of the composite anion adsorbent.
[0077] Example 6
[0078] This embodiment provides a composite anion adsorbent and a preparation method thereof, the preparation method comprising the following steps:
[0079] S1. A metal ion solution containing trivalent aluminum ions and divalent calcium ions and magnesium ions is added to a sodium hydroxide solution with a concentration of 5 mol / L for mixed hydrolysis, wherein the concentration of the trivalent metal ions is 1.5 mol / L, the molar ratio of the divalent metal ions to the trivalent metal ions is 0.2:1, the mixed hydrolysis time is 0.2 h, the mixed hydrolysis temperature is 60 ° C, the mixed hydrolysis pH is 13, and the mixed hydrolysis is immediately separated from the liquid and washed to obtain a precursor;
[0080] S2. The precursor was added to vanadium-containing wastewater with a pH value of 7 and aged at 50°C for 6 hours. After the aging, the residual vanadium-containing wastewater was washed with water, and then a sodium hydroxide solution with a mass concentration of 7% was added and activated at 30°C for 6 hours. After the activation, the residual sodium hydroxide solution was washed with water to obtain a particle size of 3.3nm and a specific surface area of 457m 2 / g of the composite anion adsorbent.
[0081] Example 7
[0082] This embodiment provides a composite anion adsorbent and a preparation method thereof, the preparation method comprising the following steps:
[0083] S1. A metal ion solution containing trivalent chromium ions, iron ions and aluminum ions and divalent magnesium ions is added to a sodium hydroxide solution with a concentration of 8 mol / L for mixed hydrolysis, wherein the concentration of the trivalent metal ions is 0.75 mol / L, the molar ratio of the divalent metal ions to the trivalent metal ions is 0.25:1, the mixed hydrolysis time is 0.75 h, the mixed hydrolysis temperature is 75 ° C, the mixed hydrolysis pH is 7, and the mixed hydrolysis is immediately separated from the solid and liquid and washed to obtain a precursor;
[0084] S2. The precursor was added to vanadium-containing wastewater with a pH value of 4 and aged at 80°C for 8 hours. After the aging, the residual vanadium-containing wastewater was washed with water, and then a sodium hydroxide solution with a mass concentration of 9% was added and activated at 25°C for 10 hours. After the activation, the residual sodium hydroxide solution was washed with water to obtain a particle size of 2.9 nm and a specific surface area of 428 m 2 / g of the composite anion adsorbent.
[0085] Example 8
[0086] This embodiment provides a composite anion adsorbent and a preparation method thereof, the preparation method comprising the following steps:
[0087] S1. A metal ion solution containing trivalent iron ions, aluminum ions and divalent magnesium ions is added to a sodium hydroxide solution with a concentration of 2 mol / L for mixed hydrolysis, wherein the concentration of the trivalent metal ions is 0.5 mol / L, the molar ratio of the divalent metal ions to the trivalent metal ions is 1:1, the mixed hydrolysis time is 0.5 h, the mixed hydrolysis temperature is 60 ° C, the mixed hydrolysis pH is 14, and the mixed hydrolysis is immediately followed by solid-liquid separation and washing to obtain a precursor;
[0088] S2. The precursor was added to a sodium chromate leachate with a pH value of 6 and aged at 95°C for 4 hours. After the aging, the residual sodium chromate leachate was washed with water, and then a sodium hydroxide solution with a mass concentration of 4% was added and activated at 45°C for 5 hours. After the activation, the residual sodium hydroxide solution was washed with water to obtain a particle size of 4.6 nm and a specific surface area of 396 m 2 / g of the composite anion adsorbent.
[0089] Example 9
[0090] This embodiment provides a composite anion adsorbent and a preparation method thereof, the preparation method comprising the following steps:
[0091] S1. A metal ion solution containing trivalent chromium ions, iron ions and aluminum ions and divalent calcium ions and magnesium ions is added to a sodium hydroxide solution with a concentration of 15 mol / L for mixed hydrolysis, wherein the concentration of the trivalent metal ions is 1.2 mol / L, the molar ratio of the divalent metal ions to the trivalent metal ions is 0.075:1, the mixed hydrolysis time is 0.3 h, after hydrolysis, the mixed hydrolysis temperature is 80 ° C, the mixed hydrolysis pH value is 10, and the mixed hydrolysis is immediately separated from the liquid and washed to obtain a precursor;
[0092] S2. The precursor was added to a sodium chromate leachate with a pH value of 5, and aged at 70°C for 7 hours. After the aging, the residual sodium chromate leachate was washed with water, and then a sodium hydroxide solution with a mass concentration of 8% was added, and activated at 50°C for 9 hours. After the activation, the residual sodium hydroxide solution was washed with water to obtain a particle size of 2.1 nm and a specific surface area of 436 m 2 / g of the composite anion adsorbent.
[0093] Example 10
[0094] The difference between this embodiment and embodiment 1 is that the molar ratio of divalent metal ions to trivalent metal ions in step S1 is 0.005:1, and the rest is the same as embodiment 1.
[0095] Embodiment 11
[0096] The difference between this embodiment and embodiment 1 is that the molar ratio of the divalent metal ion to the trivalent metal ion in step S1 is 1.1:1, and the rest is the same as embodiment 1.
[0097] Example 12
[0098] The difference between this embodiment and embodiment 1 is that the time of mixed hydrolysis in step S1 is 0.05 h, and the rest is the same as embodiment 1.
[0099] Embodiment 13
[0100] The difference between this embodiment and embodiment 1 is that the mixing and hydrolysis time in step S1 is 3 hours, and the rest is the same as embodiment 1.
[0101] Embodiment 14
[0102] The difference between this embodiment and embodiment 1 is that the temperature of the mixed hydrolysis in step S1 is 20° C., and the rest is the same as embodiment 1.
[0103] Embodiment 15
[0104] The difference between this embodiment and embodiment 1 is that the temperature of the mixed hydrolysis in step S1 is 100° C., and the rest is the same as embodiment 1.
[0105] Example 16
[0106] The difference between this embodiment and embodiment 1 is that the pH value of the mixed hydrolysis in step S1 is 4, and the rest is the same as embodiment 1.
[0107] Embodiment 17
[0108] The difference between this embodiment and embodiment 1 is that the pH value of the mixed hydrolysis in step S1 is 16, and the rest is the same as embodiment 1.
[0109] Embodiment 18
[0110] The difference between this embodiment and embodiment 1 is that in step S1, solid-liquid separation and washing are performed after waiting for 1 hour after the mixed hydrolysis is completed, and the rest is the same as embodiment 1.
[0111] Embodiment 19
[0112] The difference between this embodiment and embodiment 1 is that the pH value of the sodium chromate leaching solution in step S2 is 1, and the rest is the same as embodiment 1.
[0113] Embodiment 20
[0114] The difference between this embodiment and embodiment 1 is that the pH value of the sodium chromate leaching solution in step S2 is 13, and the rest is the same as embodiment 1.
[0115] Embodiment 21
[0116] The difference between this embodiment and embodiment 1 is that the aging temperature in step S2 is 20° C., and the rest is the same as embodiment 1.
[0117] Embodiment 22
[0118] The difference between this embodiment and embodiment 1 is that the aging temperature in step S2 is 100° C., and the rest is the same as embodiment 1.
[0119] Embodiment 23
[0120] The difference between this embodiment and embodiment 1 is that the aging time in step S2 is 0.5 h, and the rest is the same as embodiment 1.
[0121] Embodiment 24
[0122] The difference between this embodiment and embodiment 1 is that the aging time in step S2 is 11 hours, and the rest is the same as embodiment 1.
[0123] Embodiment 25
[0124] The difference between this embodiment and embodiment 1 is that the mass concentration of the sodium hydroxide solution in step S2 is 1%, and the rest is the same as embodiment 1.
[0125] Embodiment 26
[0126] The difference between this embodiment and embodiment 1 is that the mass concentration of the sodium hydroxide solution in step S2 is 11%, and the rest is the same as embodiment 1.
[0127] Embodiment 27
[0128] The difference between this embodiment and embodiment 1 is that the activation temperature in step S2 is 20° C., and the rest is the same as embodiment 1.
[0129] Embodiment 28
[0130] The difference between this embodiment and embodiment 1 is that the activation temperature in step S2 is 100° C., and the rest is the same as embodiment 1.
[0131] Embodiment 29
[0132] The difference between this embodiment and embodiment 1 is that the activation time in step S2 is 0.5 h, and the rest is the same as embodiment 1.
[0133] Embodiment 30
[0134] The difference between this embodiment and embodiment 1 is that the activation time in step S2 is 11 hours, and the rest is the same as embodiment 1.
[0135] Comparative Example 1
[0136] The difference between this comparative example and Example 1 is that in step S1, divalent calcium ions and magnesium ions are not added to the metal ion solution, and only trivalent chromium ions and iron ions are retained in the metal ion solution. The rest is the same as Example 1.
[0137] Comparative Example 2
[0138] The difference between this comparative example and Example 1 is that only the process of step S1 is retained, and the process of step S2 is not performed, and the precursor is directly used as the adsorbent material. The rest is the same as Example 1.
[0139] The composite anion adsorbent prepared in the above embodiment and the adsorbent prepared in the above comparative example were used to recover vanadium from different types of adsorption stock solutions. The results of the adsorption stock solution composition and the adsorption capacity of vanadium and chromium are shown in Table 1:
[0140] Table 1
[0141]
[0142]
[0143] From Table 1, we can see the following conclusions:
[0144] (1) Compared with Examples 10 to 18 and Comparative Example 1, the adsorption capacity and selectivity of the composite anion adsorbent prepared in Example 1 are better than those in Examples 10 to 18. It can be seen that the divalent metal ions used in the present invention will interfere with the complete formation of the crystal lattice of the trivalent metal ion crystalline hydrate, thereby facilitating the formation of non-crystalline hydrates to enhance the adsorption effect. In addition, the present invention can achieve rapid hydrolysis reaction and avoid the formation of crystalline hydrated oxides by further optimizing the molar ratio of multivalent metal ions with different valences, hydrolysis temperature, pH value, mixing time, and solid-liquid separation immediately after the mixed hydrolysis. Thus, a hydrated oxide precursor with small particle size, non-crystalline, large specific surface area and high adsorption active sites is obtained.
[0145] (2) Compared with Examples 19 to 24 and Comparative Example 2, the adsorption capacity and selectivity of the composite anion adsorbent prepared in Example 1 are better than those in Examples 19 to 24. It can be seen that the hydrated oxide precursor provided by the present invention, which has small particle size, non-crystalline, large specific surface area and a large number of hydroxyl active adsorption sites, further enhances its own stability under the synergistic effect of many conditions such as the preferred composition of the original solution to be adsorbed, pH value, aging temperature and aging time, that is, reduces the formation of crystalline hydrates, which is beneficial to improve the adsorption effect of the adsorbent.
[0146] (3) Compared with Examples 25 to 30 and Comparative Example 2, the adsorption capacity and selectivity of the composite anion adsorbent prepared in Example 1 are better than those in Examples 25 to 30. It can be seen that the hydrated oxide precursor provided by the present invention that has completed coordination exchange with vanadate anions, under the combined action of the preferred activation base concentration, activation temperature and activation time, the alkali solution and the coordinated vanadate anions are efficiently exchanged without producing crystalline hydrates, thereby further improving the adsorption effect.
[0147] In summary, the composite anion adsorbent prepared in Examples 1 to 9 of the present invention can be used for the adsorption and recovery of vanadium resources in vanadium-containing wastewater, stone coal vanadium extraction leaching solution and sodium chromate leaching solution under various conditions (pH value in the range of 2-12), and the adsorbent can not only maintain high stability under different pH conditions, but also has a high adsorption capacity and good adsorption selectivity for vanadium ions, specifically, the V2O5 adsorption capacity is not less than 120 mg / g, and the adsorption V2O5 / Cr mass ratio is greater than 35.
[0148] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a composite anion adsorbent, characterized in that: The method comprises the following steps: S1. A metal ion solution containing a first polyvalent metal ion and a second polyvalent metal ion is mixed and hydrolyzed with an alkali solution to obtain a precursor, wherein the valence of the first polyvalent metal ion is different from the valence of the second polyvalent metal ion; S2. The precursor and the original solution to be adsorbed are mixed, and the composite anion adsorbent is obtained after aging and activation treatment in sequence.
2. The method according to claim 1, characterized in that In step S1, the first multivalent metal ion includes a trivalent metal ion; Preferably, the trivalent metal ion includes any one of chromium ion, iron ion or aluminum ion, or a combination of at least two thereof; Preferably, the concentration of trivalent metal ions in the metal ion solution is 0.01 mol / L-1.5 mol / L; Preferably, the second multivalent metal ion comprises a divalent metal ion; Preferably, the divalent metal ions include magnesium ions and / or calcium ions; Preferably, the molar ratio of the second multivalent metal ion to the first multivalent metal ion is (0.01-1):1, preferably (0.05-0.3):1; Preferably, the concentration of the alkali solution in step S1 is 1 mol / L-20 mol / L, preferably 5 mol / L-15 mol / L.
3. The method according to claim 1 or 2, characterized in that: The mixed hydrolysis method in step S1 includes adding the metal ion solution containing the first polyvalent metal ion and the second polyvalent metal ion to the alkali solution, or adding the alkali solution to the metal ion solution containing the first polyvalent metal ion and the second polyvalent metal ion, or adding the metal ion solution containing the first polyvalent metal ion and the second polyvalent metal ion and the alkali solution in parallel, preferably adding the metal ion solution containing the first polyvalent metal ion and the second polyvalent metal ion to the alkali solution; Preferably, the time of the mixed hydrolysis in step S1 is 0.1h-2h, preferably 0.2h-1h; Preferably, the temperature of the mixed hydrolysis in step S1 is 25°C-95°C, preferably 50°C-80°C; Preferably, the pH value of the mixed hydrolysis in step S1 is 5-14; Preferably, solid-liquid separation is performed immediately after the mixed hydrolysis in step S1 is completed.
4. The method according to any one of claims 1 to 3, characterized in that: The raw solution to be adsorbed in step S2 includes any one of vanadium-containing wastewater, stone coal vanadium extraction leaching solution or sodium chromate leaching solution; Preferably, the pH value of the raw solution to be adsorbed in step S2 is 2-12; Preferably, the aging temperature in step S2 is 25°C-95°C, preferably 50°C-80°C; Preferably, the aging time in step S2 is 1h-10h; Preferably, washing treatment is performed after the aging in step S2 is completed.
5. The method according to any one of claims 1 to 4, characterized in that The activated reagent in step S2 includes alkali solution; Preferably, the mass concentration of the alkali solution used for activation in step S2 is 2%-10%; Preferably, the activation temperature in step S2 is 25°C-95°C, preferably 25°C-50°C; Preferably, the activation time in step S2 is 1h-10h; Preferably, washing treatment is performed after the activation in step S2 is completed.
6. The method according to any one of claims 1 to 5, characterized in that The method comprises the following steps: S1. A metal ion solution containing trivalent metal ions and divalent metal ions is added to an alkali solution with a concentration of 5mol / L-15mol / L for mixed hydrolysis, wherein the concentration of the trivalent metal ions is 0.01mol / L-1.5mol / L, the molar ratio of the divalent metal ions to the trivalent metal ions is (0.05-0.3): 1, the mixed hydrolysis time is 0.2h-1h, the mixed hydrolysis temperature is 50°C-80°C, the mixed hydrolysis pH is 5-14, and the mixed hydrolysis is immediately separated into solid and liquid to obtain a precursor; S2. Add the precursor to the original solution to be adsorbed, the pH value of the original solution to be adsorbed is 2-12, and age it at 50℃-80℃ for 1h-10h, wash it after aging, and then add alkaline solution with a mass concentration of 2%-10%, activate it at 25℃-50℃ for 1h-10h, wash it after activation to obtain the composite anion adsorbent.
7. The method according to any one of claims 1 to 6, characterized in that The composite anion adsorbent selectively adsorbs at least one of vanadate, silicate, phosphate or arsenate.
8. A composite anion adsorbent, characterized in that: The composite anion adsorbent is prepared by the method for preparing a composite anion adsorbent according to any one of claims 1-7.
9. The composite anion adsorbent according to claim 8, characterized in that: The particle size of the composite anion adsorbent is 1nm-5nm; Preferably, the specific surface area of the composite anion adsorbent is 380 m 2 / g-473m 2 / g.
10. Use of a composite anion adsorbent according to any one of claims 1 to 7, characterized in that: The composite anion adsorbent is used for adsorbing and recovering vanadium from any one of vanadium-containing wastewater, stone coal vanadium extraction leaching solution or sodium chromate leaching solution.
Citation Information
Patent Citations
Process for extracting vanadium by acid leaching of stone coal
CN101760651A
Method for recycling vanadium and chromium from high-chromium low-vanadium vanadium precipitation wastewater
CN102337411A
Stone coal vanadium extraction production process
CN111455163A
Hydrated chromic oxide adsorbent and preparation method and application thereof
CN113198414A
Method for removing foreign ions in sodium dichromate mother liquor by hydrated chromic oxide
CN116715270A